Hydroxychloroquine plus personal protective equipment versus personal protective equipment alone for the prevention of laboratory-confirmed COVID-19 infections among healthcare workers: a multicentre, parallel-group randomised controlled trial from India - Rohina Joshi; Sudha Vidyasagar; Niveditha Devasenapathy; Rinaldo Bellomo; Vivekanand Jha; Chirag Patel; Vijay Kumar; Lachlan Donaldson; Oommen John; Balasubramanian Venkatesh; Michael John; Naomi Hammond; et al. (BMJ Open)
Objectives To determine whether hydroxychloroquine when used with personal protective equipment reduces the proportion of laboratory-confirmed COVID-19 among healthcare workers in comparison to the use of personal protective equipment alone.Design Multicentre, parallel-group, open-label randomised trial. Enrolment started on 29 June 2020 and stopped on 4 February 2021. Participants randomised in HydrOxychloroquine Prophylaxis Evaluation were followed for 6 months.Setting 9 hospitals across India.Participants Healthcare workers in an environment with exposure to COVID-19 were randomised in a 1:1 ratio to hydroxychloroquine plus use of personal protective equipment or personal protective equipment alone. 886 participants were screened and 416 randomised (213 hydroxychloroquine arm and 203 personal protective equipment).Intervention Participants in intervention arm received 800 mg of hydroxychloroquine on day of randomisation and then 400 mg once a week for 12 weeks in addition to the use of personal protective equipment. In the control arm, participants continued to use personal protective equipment alone.Main outcome Proportion of laboratory-confirmed COVID-19 in the 6 months after randomisation.Results Participants were young (mean age 32.1 years, SD 9.1 years) with low-comorbid burden. 47.4% were female. In the 6 months after randomisation (primary analysis population=413), 11 participants assigned to the hydroxychloroquine group and 12 participants assigned to the standard practice group met the primary endpoint (5.2% vs 5.9%; OR 0.85, 95% CI 0.35 to 2.07, p=0.72). There was no heterogeneity of treatment effect in any prespecified subgroup. There were no significant differences in the secondary outcomes. The adverse event rates were 9.9% and 6.9% in the hydroxychloroquine and standard practice arms, respectively. There were no serious adverse events in either group.Conclusions and relevance Hydroxychloroquine along with personal protective equipment was not superior to personal protective equipment alone on the proportion of laboratory-confirmed COVID-19. Definitive conclusions are precluded as the trial stopped early for futility, and hence was underpowered.Trial registration number CTRI/2020/05/025067.